2009
DOI: 10.1088/0004-6256/137/5/4296
|View full text |Cite
|
Sign up to set email alerts
|

The Active Centaurs

Abstract: The Centaurs are recent escapees from the Kuiper belt that are destined either to meet fiery oblivion in the hot inner regions of the Solar system or to be ejected to the interstellar medium by gravitational scattering from the giant planets. Dynamically evolved Centaurs, when captured by Jupiter and close enough to the Sun for near-surface water ice to sublimate, are conventionally labeled as "short-period" (specifically, Jupiter-family) comets. Remarkably, some Centaurs show comet-like activity even when far… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
339
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(374 citation statements)
references
References 67 publications
34
339
0
1
Order By: Relevance
“…This is similar to the dust environment assumed for several SPC tails (see a summary in Fulle 1999) and for active Centaurs (Jewitt 2009).…”
Section: Dust Mass Production Ratesupporting
confidence: 82%
See 1 more Smart Citation
“…This is similar to the dust environment assumed for several SPC tails (see a summary in Fulle 1999) and for active Centaurs (Jewitt 2009).…”
Section: Dust Mass Production Ratesupporting
confidence: 82%
“…The method is derived from the one used by Jewitt (2009) to compute the dust production rate of active Centaurs in the region between 5 and 12 AU; it was adapted and already successfully applied by our group to cometary environment. We refer to Geometric albedo p R : we adopted the typical value for comet nuclei of p R = 0.04; this is an important factor in the uncertainty in our calculations since the actual albedo of dust grains is unknown.…”
Section: Dust Mass Production Ratementioning
confidence: 99%
“…This comet was study by Mazzotta Epifani & Palumbo (2011) in its previous perihelion passage in October 2004. The authors estimated that the dust production rate at perihelion with values within Q d = 14−345 kg s −1 using a method derived from the one used by Jewitt (2009) to compute the dust production rate of active Centarus. They also obtained A f ρ = 846 ± 55 cm in an aperture of radius ρ = 7.3 × 10 3 km, and they concluded that this comet is more active than the average at a given heliocentric distance.…”
Section: Discussionmentioning
confidence: 99%
“…The method is derived from the one used by Jewitt (2009) to compute the dust production rate of active Centaurs in the region between 5 and 12 AU, and was already successfully applied to estimating the dust production rate of the Oort comet C/2007 D1 (LINEAR) (Mazzotta Epifani et al 2010). The method consists of computing the apparent magnitude of the pure coma m d in an annulus between an inner φ and a conveniently chosen outer φ as…”
Section: Dust Mass Production Ratementioning
confidence: 99%